Ostracism and twitter : the relationship of gender, self-esteem and extraversion on micro-blogging. - Ho, Jun Hao. (2010)
Previous studies concluded that ostracism will lead to much distress. However, not much research is being done on the relationship between blogging and ostracism. Sixty undergraduate students were divided into two conditions (ostracised versus non-ostracised), and Cyberball was used to evoke the effect of ostracism, while Twitter was employed as a mean to gauge for ostracism. Result shows that ostracised participants displayed higher need for Affiliation, and gender differences on the need for Affiliation, Power and Achievement had partly been observed. However, ostracised participants and individuals who had higher negative affect did not tweet more to relief their feelings. Also, no significant effect was found for self-esteem and extraversion between users on their number of tweets.